PENDAMPINGAN PEMASARAN ONLINE PADA KELOMPOK USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) DI KECAMATAN LOWOKWARU KOTA MALANG - Nuraini, Ida; Susilowati, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The Covid 19 pandemic has an impact on the decline in sales of Micro, Small and Medium Enterprises (MSMEs) because most MSMEs cannot sell their products freely due to physical distancing policies and Large-Scale Social Restrictions. Meanwhile, many MSMEs have not been able to sell their products online because they do not have the skills to sell online. The purpose of this community service is training and online marketing assistance to the Business Group for Increasing Prosperous Family Income (UPPKS) in Lowokwaru District. The method of implementing activities is training to create business Instagram and Facebook accounts, techniques for taking photos of products, producing marketing videos, uploading product photos, tips on finding consumers, packaging techniques and product delivery. Partners are “atiqa” UPPKS members who produce handicrafts such as bags, wallets, tissue holders and mask. The result of the activity for 6 months was the joining of partners at the Shopee market place, active Instagram and business Facebook. Sales increase during the Covid 19 pandemic due to partners producing mask. The gross revenue from 1,500,000 rupiah per month increases to 3,000,000-6,500,000 rupiah per month. Online sales can expand the marketing area, unlimited sales of time so as to increase sales.It is hope that other UPPKS members and MSMEs can sell online in order to increase revenue. Keywords : Online marketing, Market place, Handicrafts